A syntactic analysis of the Portela Urbanization using prolog - Fernandes, Pedro Afonso (2021)
Portela is a paradigmatic modern housing complex located at the vicinity of Lisbon. Developed since the late 1960s, it combines several syntactic schemes, namely, concentric towers, asymmetric blocks and primary open-closed cells typically distributed along a ring-shaped road. It is also structured by a central space with a mall and other facilities. In this paper we introduce Prolog, a Logic Programming language used in Artificial Intelligence, to describe the internal logic of Portela Urbanization. Firstly, we explain how the syntactic schemes present in Portela can be generated in a recursive way using Prolog and following an approach like the ideographic language introduced by Bill Hillier and Julienne Hanson in their seminal book The Social Logic of Space (1984). Secondly, we performed a settlement (alpha) analysis of Portela by computing connectivity, control, depth, integration and other syntactic measures using Prolog predicates. These two complementary approaches proved to be useful to understand the ideal of the Modern city as far as the Portela complex is concerned. And show how Logic Programming is a useful tool to describe the patterns of discrete systems as social knowables due to its declarative nature. In fact, a Prolog program represents a certain amount of knowledge, namely, of an urban settlement (or building), which is used to answer queries about the social and economic consequences of some spatial design.